The Enhancement of Oral Mediation Competence via Revoicing Practice: Learners Lending their Voice and Eyes to Diverse Audiences for Dubbing and Audio Description Tasks - Sánchez-Requena, Alicia; Navarrete, Marga (Journal of Audiovisual Translation, 2024)
Oral production plays a vital role in summative and formative foreign language (FL) examinations. Assessment rubrics to gauge oral skills are constantly developing to facilitate their understanding and evaluation. Nonetheless, there is a gap between research findings and teaching resources available (Levis, 2016). The present paper seeks to contribute to this disparity by comparing two action research studies that evidenced the benefits of using revoicing as a tool to improve speaking in spontaneous conversations. Over a hundred learners of Spanish as a FL actively dubbed or audio described videoclips as a classroom activity for several weeks. Results were triangulated and included both qualitative and quantitative data, evincing that oral productive skills are enhanced when these revoicing modes are incorporated into the teaching material. Both studies bring forward a comparison between the similarities and differences in the results, and they thoroughly review their limitations and provide relevant future lines of research. Lay summary This paper is addressed to researchers and practitioners in language learning who are interested in the enhancement of oral speech through dubbing and audio description practice. Speaking and oral production are a crucial part of formal and non-formal foreign language (FL) examinations. Assessments and rubrics are constantly developing to reduce subjectivity. There is agreement that defining the thorny elements that involve speaking facilitates understanding and evaluation. However, there is still a gap between research findings and teaching resources available. The present paper seeks to contribute to this disparity by comparing two action research studies that evidenced the benefits of using revoicing (speaking practice using clips) as a tool to improve spontaneous conversations. Over a hundred learners of Spanish as a FL actively dubbed or audio described the clips presented for several weeks. Results were triangulated and included both qualitative and quantitative data, evincing that oral productive skills are enhanced by these revoicing modes. The conclusions draw a comparison between the similarities and differences between the results in both studies, they thoroughly review their limitations and provide relevant future lines of research on the field.